Perbaikan Tanah Labil dengan menggunakan Mineral Kapur sebagai Pendukung Pondasi Dasar Jalan Raya - Gustaf Gautama (Balitbangda Provinsi Lampung, 2016)
Soil is an important part of a construction which has the function of supporting the construction above , the material making up ground in the form of minerals, organic matter and sediments are relatively loose. Based on the geographical location of a place, soil type , soil characteristics and properties are different, so that not all soil can be used for construction. One of them clay soil types that have properties of elasticity and high porosity so that it will lead to roads was cracked and bumpy if used as the basis for the foundation of the highway because of unstable ground. It is necessary for research in order to clay can be stabilized. The addition of lime by 6 % , 8 % , 10 % , 12 % and 15 % of per cent by weight and the addition of 5% water mixed with molasses as much as 20 % of the weight of the water and will produce a fairly small porosity of 12.29 % in Extra 15 % lime and a small water absorption of 7.56 and a high enough density of 1.75 will result in hard ground and the meeting so that the pores of the clay into a meeting and the soil becomes hard by slaging reaction occurs between the silica and lime and molasses binder. The effect of stabilization on clay -type soil , the land will be stabilized and hard so that it can be used as the basis for the foundation of a highway.